EVALUATION OF STRATEGIES TO STRENGTHEN HOSPITAL RISK MANAGEMENT THROUGH THE IMPLEMENTATION OF CLINICAL RISK MANAGEMENT AT MURNI TEGUH MEMORIAL HOSPITAL - Darma Abdinta Sitepu; Ermi Girsang; Sri Lestari Ramadhani Nasution (Journal of Gender and Social Inclusion in Muslim Societies, 2026)
This study aims to evaluate the strategy for strengthening hospital risk management through the implementation of Clinical Risk Management (CRM) at Murni Teguh Memorial Hospital (MTMH). The research utilized a qualitative descriptive approach, with data collected through in-depth interviews, observations, and document reviews involving eight key informants from hospital management and clinical units. The findings reveal that while clinical risk identification and analysis are systematically conducted using incident reporting, clinical audits, and analytical tools like RCA and FMEA, operational challenges such as underreporting and high staff workloads remain. To address these issues, this study identified a five-pillar integrated CRM reinforcement model combining top-down and bottom-up approaches: leadership and risk governance, integrated CRM processes, human resource competency enhancement, a non-punitive safety culture, and continuous monitoring and evaluation. The implementation of this strategy has significantly improved the incident reporting culture, interprofessional coordination, and staff risk awareness. This demonstrates that strong top management commitment is crucial for sustaining patient safety improvements.